Prediction of tablet weight variability in continuous manufacturing - Razavi, Sonia M.; Scicolone, James; Snee, Ronald D.; Kumar, Ashish; Bertels, Johny; Cappuyns, Philippe; Van Assche, Ivo; Cuitiño, Alberto M.; Muzzio, Fernando (International journal of pharmaceutics, 2020)
[Display omitted] This paper provides a method for prediction of weight variability of tablets made in rotary tablet presses as a function of material attributes and processing parameters. The goal was to be able to predict whether or not a formulation is suitable for direct compaction continuous manufacturing using the tablet weight variability as a criterion. The work focused on identifying the significant factors affecting the weight variability in tablets, within the design space studied. A wide range of blends with different powder properties were prepared. It was shown that among powder properties, cohesion, bulk density, and particle size were the most significant and sufficient material attributes to explain tablet weight variability. A response surface model was built and validated with three different blends. The model is not formulation dependent and can be expanded to include other blend properties or processing parameters effects.